The Potency of Olive Oil, Coconut Oil, and Bleached Palm Oil as Clearing Agent in Histological Preparation - Ruth Liananda Citra Dolok Saribu; Laili Mufli Zusrina; Murtiadi Erlan Supraitno; Ardaning Nuriliani; Bambang Retnoaji; Hendry T.S.S.G. Saragih; Zuliyati Rohmah (Berkala Ilmiah Biologi, 2023)
Clearing is an important process in histological preparations. The aim of the clearing process is to remove alcohol from the tissues upon dehydration. The most commonly used clearing agent is xylol, however it is known that there are negative effects from using xylol. This literature study purpose to study the potential of three vegetable oils, i.e., olive oil, coconut oil, and refined palm oil, as clearing agents to replace xylol. This literature study was conducted using search engines such as Semantic Scholar, NCBI, ICAMS, IJPRSE, JOMFP, PubMed, and ResearchGate with the keywords olive oil, coconut oil, palm oil, xylol, clearing agent, and histological preparations. There is no year limitation of references in this literature study. Based on the literatures, it is known that the use of olive oil as a clearing agent produces similar histological preparation qualities to xylol. This can be seen from several criteria that were measured, including the level of tissue translucency and the ability to maintain the quality of the staining. Similar results were shown by purified coconut oil and palm oil, both of which can produce tissues with optimal levels of transparency. The conclusion from this literature study is that refined olive oil, coconut oil, and palm oil can be used as clearing agents for xylol substitutes that are safer for researchers and the environment.